Sexual Fluidity: An Integrative Review - Hunt, Steve; Hunt, Elena (European Scientific Journal, ESJ, 2018)
Historically, sexuality had been considered a fundamental, biologically determined characteristic of humans. Lately, better protection of human rights and recognition of non-traditional relationships have been leading to acceptance towards gay, transgendered and bisexual people. Nonetheless, little advancement has been made into fully understanding the intricacies of human sexuality and recent research has found that sexuality may not be fixed after all; instead, it appears to be more variable and fluid. This integrative review on sexual fluidity has drawn four discussed themes: Sexuality as a Continuum, Sexual Fluidity of Women, Sexual Agency and Hetero/Homosexuality Binary of Men. Several questions call for more research into understanding sexual fluidity across the lifespan and the development of initiatives to help individuals to both understand and accept this trait. Furthermore, advocacy is needed to ensure equal rights and freedoms without discrimination, both socially and economically.